Method for constructing aluminum oxide and boron nitride fiber skeleton aerogel material based on ultra-concentrated emulsion
The composite three-dimensional network structure of boron nitride aerogel and alumina fiber was constructed through the super-concentrated emulsion template method, which solved the problems of poor mechanical properties and limited flexibility of boron nitride aerogel, and achieved high-performance isolation at extreme temperatures Thermal and mechanical properties are improved.
Patent Information
- Application Number
- CN202411641633.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-10
AI Technical Summary
The existing boron nitride aerogels have poor mechanical properties and limited flexibility and are not resistant to high temperatures, which limits their application in extreme environments.
The ultra-concentrated emulsion template method was used to assemble the boron nitride aerogel and the modified alumina fibers in wet chemical method to build a composite three-dimensional porous network structure to enhance its flexibility and robustness.
The flexibility and robustness of boron nitride aerogel has been improved, and can withstand different forms of loads in ultra-low and ultra-high temperature environments, and regulate its density and porosity to meet the thermal insulation and mechanical performance requirements of different application scenarios. .
Smart Images

Figure CN119285366A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel material preparation, and in particular to a method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super concentrated emulsion. Background Art
[0002] Aerogel is a unique solid material consisting of an interconnected three-dimensional network structure and a large number of air-filled pores, which extend the structural characteristics and physical and chemical properties of nanoscale building blocks to the macroscopic scale. As a new type of material with a unique micro-nanoporous structure, aerogel has the advantages of low density, large specific surface area, high porosity, and low thermal conductivity. In particular, aerogel is one of the best thermal insulation materials in the world today. Its ultra-light and ultra-fine porous structure makes it almost impossible for heat to conduct, thus achieving an extremely high thermal insulation effect. This characteristic makes aerogel widely used in aerospace, building energy conservation, equipment insulation, aerospace, oil pipelines and special environments.
[0003] Silica aerogel, polymer aerogel, metal aerogel, carbide aerogel, boron nitride aerogel, etc. have greatly enriched the family of aerogels and expanded the research field and application scenarios of aerogels. However, the thermal insulation and mechanical properties of current aerogels have certain defects, mainly because their thermal conductivity increases rapidly: under high temperature conditions, the thermal conductivity of aerogels will increase significantly, which limits their application effect in high temperature environments. Secondly, poor mechanical strength: the low density of aerogels leads to weak mechanical strength and is easily crushed or damaged, which is a major disadvantage in application scenarios that require higher mechanical strength. Poor adhesion: aerogels have poor adhesion to reinforcing matrix materials such as fibers, which affects their application effect in composite materials. Therefore, it is very necessary to construct aerogel materials that are flexible and have excellent thermal insulation properties in extreme environments.
[0004] Boron nitride is a crystal composed of the same number of nitrogen atoms and boron atoms, with excellent insulation, chemical stability and thermal stability. In simple terms, boron nitride aerogel is a material with a unique structure and excellent performance. Boron nitride aerogel combines the advantages of microscopic and macroscopic materials. However, most literature only shows that the microstructure of boron nitride aerogel is composed of micro-nanobelts, and its mechanical properties and ultra-high temperature resistance are limited due to its single nanobelt microstructure. At present, the mechanical properties of boron nitride still have huge defects. Its brittleness, weak mechanical strength and limited flexibility seriously limit the application of aerogels.
[0005] So far, there are few reports on the deep winding of boron nitride aerogel micro-nanobelts with other types of fibers to prepare flexible aerogels. In the preparation process of boron nitride aerogel, the gelation process is the key link in the preparation of aerogel, because it almost determines the final form of the aerogel, and the fibers form good dispersion and bonding during the gelation process. The traditional gelation process follows the classic sol-gel process to form a disordered, continuous colloidal network. The superconcentrated emulsion template method has a simple preparation process, low solvent consumption, and low energy consumption in the drying process. It regulates and obtains supramolecular aggregates with different microstructures in the wet chemical stage, and then converts them into boron nitride at high temperature. Due to the regulation process in the wet chemical stage, the final product obtained by this method has a very excellent porous microstructure; at the same time, the obtained materials have diversity and adjustability in specific properties and microfibers. The superconcentrated emulsion template method combines the advantages of emulsion and gel, making the foam structure and gel state of the emulsion itself an ideal template for the preparation of boron nitride aerogel, and at the same time, the advantages of supramolecular assembly are utilized to adjust the final performance. However, there has never been a report on the use of supramolecular assembly methods to achieve ultra-flexibility and high-temperature resistance of boron nitride aerogel materials assembled with boron nitride materials and different fibers. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super-concentrated emulsion in view of the deficiencies of the above-mentioned prior art. The method uses a super-concentrated emulsion template method to perform wet chemical supramolecular assembly of boron nitride aerogel and modified alumina fiber, so that the two can construct and weave a three-dimensional framework on a micro-nano scale, interweave and entangle with each other to form a composite three-dimensional porous network structure, thereby having excellent flexibility and robustness, and resistance to ultra-low and ultra-high temperatures, solving the shortcomings of the existing boron nitride aerogel, which has poor mechanical properties, limited flexibility, and is not resistant to high temperatures.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super concentrated emulsion, characterized in that the method comprises the following steps:
[0008] Step 1, preparing boron nitride aerogel: at room temperature, mixing a boron source small molecule, a nitrogen source small molecule and a solvent to obtain a precursor solution, then shaking the precursor solution and subjecting it to low temperature treatment, triggering a sol-gel transition by temperature induction, obtaining a boron nitride precursor, and then freeze-drying and high-temperature pyrolysis the boron nitride precursor to obtain a boron nitride aerogel;
[0009] Step 2, preparing a super concentrated emulsion: at room temperature, dispersing alumina fibers into a polyethyleneimine aqueous solution, modifying the surface of the alumina fibers using amino groups to obtain modified alumina fibers, and then dispersing the boron nitride aerogel obtained in step 1 and the modified alumina fibers into a polyvinyl alcohol aqueous solution and mixing them with high-speed stirring to obtain a super concentrated emulsion;
[0010] Step 3: Prepare alumina boron nitride fiber skeleton aerogel material: place the super concentrated emulsion obtained in step 2 in a mold for ice template freezing, then freeze-dry, and then pyrolyze the freeze-dried product at high temperature to obtain alumina boron nitride fiber skeleton aerogel material.
[0011] The invention first obtains flexible boron nitride micro-nanobelt aerogel through sol-gel transformation, freeze drying and high-temperature pyrolysis, then disperses the aerogel and amino-modified alumina fibers in a polyvinyl alcohol aqueous solution by a superconcentrated emulsion template method, performs wet chemical supramolecular assembly through high-speed stirring polymerization, utilizes the amino groups on the modified alumina fibers to form hydrogen bonds with the hydroxyl groups on the side chains of the polyvinyl alcohol polymer, and forms a large number of hydrogen bonds in the network structure rich in polymers to enhance the network structure of the aerogel, so that the alumina fibers are dispersed and interpenetrated and entangled in the structure of the boron nitride aerogel, constructs and weaves a three-dimensional framework on a micro-nano scale, and then forms an alumina boron nitride fiber skeleton aerogel material with a composite three-dimensional porous network structure through freezing, freeze drying and high-temperature pyrolysis.
[0012] The above-mentioned method for constructing alumina boron nitride fiber skeleton aerogel material based on superconcentrated emulsion is characterized in that the boron source small molecule in step one is selected from one or more of boric acid, boric anhydride and sodium borate, the nitrogen source small molecule is selected from one or more of urea, melamine and polyethyleneimine, and the solvent is selected from one or more of distilled water, ethanol and tert-butanol.
[0013] The above-mentioned method for constructing alumina boron nitride fiber skeleton aerogel material based on super concentrated emulsion is characterized in that the preparation process of the precursor solution in step one is: dissolving the boron source small molecules and the nitrogen source small molecules in the solvent, heating to 80°C to 85°C and continuously stirring to obtain a precursor solution, and maintaining the precursor solution at 35°C to 40°C; the low-temperature treatment process is: keeping warm at below -5°C for more than 10 hours; the freeze-drying time is greater than 24 hours; the high-temperature pyrolysis process is: heating to 1000°C to 1200°C at a heating rate of 5°C / min to 10°C / min and then keeping warm for 3h to 4h.
[0014] The above-mentioned method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super-concentrated emulsion is characterized in that the mass fraction of the polyethyleneimine aqueous solution in step 2 is 1% to 5%.
[0015] The above-mentioned method for constructing alumina boron nitride fiber skeleton aerogel material based on superconcentrated emulsion is characterized in that the mass of the modified alumina fiber in step 2 is less than 40% of the mass of the polyvinyl alcohol aqueous solution, and the mass fraction of the polyvinyl alcohol aqueous solution is 5% to 20%.
[0016] The above-mentioned method for constructing an alumina boron nitride fiber skeleton aerogel material based on a superconcentrated emulsion is characterized in that in step 2, ultrasonic dispersion is used to disperse the boron nitride aerogel and the modified alumina fiber in a polyvinyl alcohol aqueous solution, and then mechanical stirring polymerization is carried out at a rotation speed of 350 rpm to 450 rpm.
[0017] The above-mentioned method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super-concentrated emulsion is characterized in that the mass ratio of the boron nitride aerogel to the modified alumina fiber in step 2 is 13:16-48.
[0018] The above-mentioned method for constructing alumina boron nitride fiber skeleton aerogel material based on super concentrated emulsion is characterized in that the high-temperature pyrolysis process in step three is: heating to 1000°C to 1200°C at a heating rate of 5°C / min to 10°C / min and then keeping warm for 3h to 4h.
[0019] The above-mentioned method for constructing alumina boron nitride fiber skeleton aerogel material based on superconcentrated emulsion is characterized in that by adjusting the mass ratio of boron nitride aerogel to modified alumina fiber in step 2, the entanglement of the modified alumina fiber and the skeleton structure of boron nitride aerogel is controlled by supramolecular assembly electrostatically, thereby adjusting the porosity.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. The present invention adopts an ultra-concentrated emulsion template method to perform wet chemical supramolecular assembly of boron nitride aerogel and modified alumina fibers, so that the alumina fibers are dispersed and interpenetrated and entangled in the boron nitride aerogel structure, and the composite of the two at the micro-nano scale is achieved, and an alumina boron nitride fiber skeleton aerogel material with a composite three-dimensional porous network structure is constructed, which not only exerts the excellent high temperature resistance of the boron nitride aerogel, but also increases its strength and flexibility. Therefore, the aerogel material has excellent flexibility and robustness, and can withstand different forms of loads within the ultra-low and ultra-high temperature ranges.
[0022] 2. The present invention adjusts the mass ratio of boron nitride aerogel and modified alumina fiber, and utilizes supramolecular assembly electrostatically to control the entanglement of the rigid modified alumina fiber and the flexible boron nitride aerogel skeleton three-dimensional structure to achieve porosity change, thereby regulating the density, porosity, and thermal conductivity of the aerogel material, and further regulating the thermal insulation and flexible mechanical properties of the aerogel material to meet the needs of different application scenarios.
[0023] 3. The alumina boron nitride fiber skeleton aerogel material prepared by the present invention exhibits good flexibility in the range of -196°C to 1200°C, can withstand loads such as compression, shearing, twisting, and stretching, and has good resilience, and is suitable for preparation into an ultra-soft film.
[0024] 4. The preparation method of the present invention has simple process, mild and green reaction conditions, low cost, and is easy to scale up for continuous production. It can be used to prepare large-area thermal insulation felt materials and has broad industrial application prospects.
[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The present invention is a process flow chart for constructing an alumina boron nitride fiber skeleton aerogel material based on a super concentrated emulsion.
[0027] Figure 2 This is a physical picture of the super concentrated emulsion prepared in Example 3 of the present invention.
[0028] Figure 3 This is a physical picture of the alumina boron nitride fiber skeleton aerogel material prepared in Example 3 of the present invention.
[0029] Figure 4 This is a microscopic image of the interior of the alumina boron nitride fiber skeleton aerogel material prepared in Example 3 of the present invention.
[0030] Figure 5 This is a rheological property curve diagram of the super concentrated emulsion prepared in Example 3 of the present invention.
[0031] Figure 6 This is a diagram showing the high temperature resistance and rebound of the alumina boron nitride fiber skeleton aerogel material prepared in Example 3 of the present invention at different compression degrees under an alcohol lamp.
[0032] Figure 7 Schematic diagram of the tensile test of the alumina boron nitride fiber skeleton aerogel material prepared in Example 3 of the present invention.
[0033] Figure 8 This is a thermal conductivity curve of the alumina boron nitride fiber skeleton aerogel material prepared in Example 3 of the present invention at different temperatures.
[0034] Fig. 9 This is the pore distribution diagram of the alumina boron nitride fiber skeleton aerogel material prepared in Example 3 of the present invention.
[0035] Fig.10 This is a schematic diagram of placing a four-leaf clover on the surface of the alumina boron nitride fiber skeleton aerogel material prepared in Example 3 of the present invention after being continuously heated at high temperature for 2 minutes.
[0036] Fig.11 The temperature change state diagram and curve diagram of the alumina boron nitride fiber skeleton aerogel material with a thickness of 20 mm prepared in Example 3 of the present invention during the heating process of 1 min to 30 min.
[0037] Fig.12 A scene diagram showing the use of the thermal insulation flexible felt made of the alumina boron nitride fiber skeleton aerogel material prepared in Example 3 of the present invention for thermal insulation.
[0038] Fig.13 This is a thermal conductivity curve of aerogel materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0039] Example 1
[0040] like Figure 1 As shown, this embodiment includes the following steps:
[0041] Step 1, preparation of boron nitride aerogel: at room temperature, 2.1g of boric acid and 2.1g of melamine were dissolved in 8.9mL of distilled water to obtain a precursor solution, and then the precursor solution was heated to 85°C and continuously stirred until the system became transparent. When cooled to room temperature, it presented a white gel-like emulsion. After standing, it was inverted and observed. The system lost fluidity, and a boron nitride precursor was obtained. The temperature was maintained at 35°C to 40°C. The boron nitride precursor was placed in a refrigerator at -5°C for 72h, and then freeze-dried for 24h to obtain a boron nitride aerogel precursor composed of micro-nanobelts, which was then placed in a tubular furnace, heated to 1200°C at a heating rate of 10°C / min, and then kept warm for 4h, and naturally cooled to room temperature to obtain a boron nitride aerogel;
[0042] Step 2, prepare a super concentrated emulsion: at room temperature, disperse 10 mg of mullite fiber into 5 mL of a 5% polyethyleneimine aqueous solution for mixing, oscillating and ultrasonicating, and use amino groups to surface modify the mullite fiber for 120 minutes, and the system is transformed into a light yellow transparent solution to obtain modified alumina fiber, and then 0.13 g of the boron nitride aerogel obtained in step 1 and 0.16 g of the modified alumina fiber solution are ultrasonically dispersed in 1 mL of a 20% polyvinyl alcohol aqueous solution, and stirred and mixed at a high speed of 450 rpm to obtain a super concentrated emulsion;
[0043] Step 3, preparing alumina boron nitride fiber skeleton aerogel material: the super concentrated emulsion obtained in step 2 is loaded into a polytetrafluoroethylene mold, and placed on the upper surface of an iron column immersed in low-temperature ethanol for freezing, and then placed in a -5°C refrigerator for 40 hours, and then freeze-dried for 48 hours to remove the ice template, and then the freeze-dried product is heated to 800°C at a heating rate of 5°C / min and kept warm for 4 hours for high-temperature pyrolysis to obtain an alumina boron nitride fiber skeleton aerogel material.
[0044] After testing, the density of the aluminum oxide boron nitride fiber skeleton aerogel material prepared in this embodiment is 0.20g / cm 3 The porosity is 89.3% and the thermal conductivity is 26.9mW / (m·K).
[0045] The boron source small molecule in this embodiment may also be one or more of boric acid, boric anhydride and sodium borate other than boric acid, the nitrogen source small molecule may also be one or more of urea, melamine and polyethyleneimine other than melamine, and the solvent may also be one or more of distilled water, ethanol and tert-butanol other than distilled water.
[0046] Comparative Example 1
[0047] This comparative example comprises the following steps:
[0048] Step 1, preparation of boron nitride aerogel: at room temperature, 2.1g of boric acid and 2.1g of melamine were dissolved in 8.9mL of distilled water to obtain a precursor solution, and then the precursor solution was heated to 80°C to 85°C and continuously stirred and shaken until the system became transparent. When cooled to room temperature, it showed a white gel-like emulsion. After standing and inverting for observation, the system lost fluidity, and a boron nitride precursor was obtained. The temperature was maintained at 35°C to 40°C, and the boron nitride precursor was placed in a refrigerator at -5°C for 60h, followed by freeze drying for 24h to obtain a boron nitride aerogel precursor composed of micro-nanobelts;
[0049] Step 2: Prepare a boron nitride fiber skeleton aerogel material: Place the boron nitride aerogel precursor obtained in step 1 in a -5°C refrigerator for 40 hours, then freeze-dry for 48 hours, and then heat the freeze-dried product to 1200°C at a heating rate of 10°C / min and keep it for 4 hours for high-temperature pyrolysis to obtain a boron nitride fiber skeleton aerogel material.
[0050] After testing, the density of the boron nitride fiber skeleton aerogel material prepared in this comparative example is 0.19g / cm 3 The porosity is 87.9% and the thermal conductivity is 28.3mW / (m·K).
[0051] Example 2
[0052] like Figure 1 As shown, this embodiment includes the following steps:
[0053] Step 1, preparation of boron nitride aerogel: at room temperature, 2.1g of boric acid and 2.1g of melamine were dissolved in 8.9mL of distilled water to obtain a precursor solution, and then the precursor solution was heated to 85°C and continuously stirred until the system became transparent. When cooled to room temperature, it presented a white gel-like emulsion. After standing, it was inverted and observed. The system lost fluidity, and a boron nitride precursor was obtained. The temperature was maintained at 35°C to 40°C. The boron nitride precursor was placed in a refrigerator at -5°C for 72h, and then freeze-dried for 24h to obtain a boron nitride aerogel precursor composed of micro-nanobelts, which was then placed in a tubular furnace, heated to 1200°C at a heating rate of 10°C / min, and then kept warm for 4h, and naturally cooled to room temperature to obtain a boron nitride aerogel;
[0054] Step 2, prepare a super concentrated emulsion: at room temperature, disperse 10 mg of mullite fiber into 5 mL of a 5% polyethyleneimine aqueous solution for mixing, oscillating and ultrasonicating, and use amino groups to surface modify the mullite fiber for 120 minutes, and the system is transformed into a light yellow transparent solution to obtain modified alumina fiber, and then 0.13 g of the boron nitride aerogel obtained in step 1 and 0.27 g of the modified alumina fiber solution are ultrasonically dispersed in 1 mL of a 20% polyvinyl alcohol aqueous solution, and stirred and mixed at a high speed of 450 rpm to obtain a super concentrated emulsion;
[0055] Step 3, preparing alumina boron nitride fiber skeleton aerogel material: the super concentrated emulsion obtained in step 2 is loaded into a polytetrafluoroethylene mold, and placed on the upper surface of an iron column immersed in low-temperature ethanol for freezing, and then placed in a -5°C refrigerator for 40 hours, and then freeze-dried for 48 hours to remove the ice template, and then the freeze-dried product is heated to 800°C at a heating rate of 5°C / min and kept warm for 4 hours for high-temperature pyrolysis to obtain an alumina boron nitride fiber skeleton aerogel material.
[0056] After testing, the density of the aluminum oxide boron nitride fiber skeleton aerogel material prepared in this embodiment is 0.22g / cm 3 The porosity is 91.4% and the thermal conductivity is 26.5mW / (m·K).
[0057] The boron source small molecule in this embodiment may also be one or more of boric acid, boric anhydride and sodium borate other than boric acid, the nitrogen source small molecule may also be one or more of urea, melamine and polyethyleneimine other than melamine, and the solvent may also be one or more of distilled water, ethanol and tert-butanol other than distilled water.
[0058] Example 3
[0059] like Figure 1 As shown, this embodiment includes the following steps:
[0060] Step 1, preparation of boron nitride aerogel: at room temperature, 2.1g of boric acid and 2.1g of melamine were dissolved in 8.9mL of distilled water to obtain a precursor solution, and then the precursor solution was heated to 85°C and continuously stirred until the system became transparent. When cooled to room temperature, it presented a white gel-like emulsion. After standing, it was inverted and observed. The system lost fluidity, and a boron nitride precursor was obtained. The temperature was maintained at 35°C to 40°C. The boron nitride precursor was placed in a refrigerator at -5°C for 72h, and then freeze-dried for 24h to obtain a boron nitride aerogel precursor composed of micro-nanobelts, which was then placed in a tubular furnace, heated to 1200°C at a heating rate of 10°C / min, and then kept warm for 4h, and naturally cooled to room temperature to obtain a boron nitride aerogel;
[0061] Step 2, prepare a super concentrated emulsion: at room temperature, disperse 10 mg of mullite fiber into 5 mL of a 5% polyethyleneimine aqueous solution for mixing, oscillating and ultrasonicating, and use amino groups to surface modify the mullite fiber for 120 minutes, and the system is transformed into a light yellow transparent solution to obtain modified alumina fiber, and then 0.13 g of the boron nitride aerogel obtained in step 1 and 0.36 g of the modified alumina fiber solution are ultrasonically dispersed in 1 mL of a 20% polyvinyl alcohol aqueous solution, and stirred and mixed at a high speed of 450 rpm to obtain a super concentrated emulsion, such as Figure 2 As shown;
[0062] Step 3, preparing alumina boron nitride fiber skeleton aerogel material: the super concentrated emulsion obtained in step 2 is loaded into a polytetrafluoroethylene mold, and placed on the upper surface of an iron column immersed in low-temperature ethanol for freezing, and then placed in a -5°C refrigerator for 40 hours, and then freeze-dried for 48 hours to remove the ice template, and then the freeze-dried product is heated to 800°C at a heating rate of 5°C / min and kept warm for 4 hours for high-temperature pyrolysis to obtain an alumina boron nitride fiber skeleton aerogel material.
[0063] After testing, the density of the aluminum oxide boron nitride fiber skeleton aerogel material prepared in this embodiment is 0.25g / cm 3 The porosity is 93.9%, the thermal conductivity is 26.1mW / (m·K), and it can withstand high temperatures of 1200°C for more than 20 minutes.
[0064] The boron source small molecule in this embodiment may also be one or more of boric acid, boric anhydride and sodium borate other than boric acid, the nitrogen source small molecule may also be one or more of urea, melamine and polyethyleneimine other than melamine, and the solvent may also be one or more of distilled water, ethanol and tert-butanol other than distilled water.
[0065] Figure 4 This is the internal microscopic image of the aluminum oxide boron nitride fiber skeleton aerogel material prepared in this embodiment. Figure 4 It can be seen that the internal microstructure of the alumina boron nitride fiber skeleton aerogel material is composed of boron nitride nanobelts or microbelts and alumina fibers entangled with each other.
[0066] Figure 5 The rheological performance curve of the super concentrated emulsion prepared in this embodiment is as follows: Figure 5 It can be seen that the super concentrated emulsion has ultra-high storage modulus and loss modulus, and the calculated loss tangent values are all around 0.1, indicating that the super concentrated emulsion has good stability.
[0067] Figure 6 This is a diagram showing the high temperature resistance and rebound of the alumina boron nitride fiber skeleton aerogel material prepared in this example at different compression levels under an alcohol lamp. Figure 6 It can be seen that the material can withstand the burning temperature of the alcohol lamp both in the unstressed state and in the rebound state immediately after compression, indicating that the aerogel material still has good high temperature resistance under large-scale stress conditions such as compression and rebound.
[0068] Figure 7 Schematic diagram of the tensile test of the aluminum oxide boron nitride fiber skeleton aerogel material prepared in this embodiment. Figure 7 It can be seen that the aerogel material can withstand a weight of 5 kg, indicating that it has excellent mechanical properties in the longitudinal direction.
[0069] Figure 8 This is a graph showing the thermal conductivity of the aluminum oxide boron nitride fiber skeleton aerogel material prepared in this example at different temperatures. Figure 8 It can be seen that the thermal conductivity of the aerogel material increases as the temperature rises, but there is no obvious increase, indicating that the thermal conductivity of the aerogel material is stable.
[0070] Fig. 9 This is the pore distribution diagram of the aluminum oxide boron nitride fiber skeleton aerogel material prepared in this example. Fig. 9 It can be seen that the pore size distribution of the aerogel material is mainly concentrated around 10 μm, indicating that the pore size distribution of the network structure of the aerogel material constructed by boron nitride fiber and alumina fiber is relatively concentrated.
[0071] Fig.10 This is a schematic diagram of a four-leaf clover placed on the surface of the aluminum oxide boron nitride fiber skeleton aerogel material prepared in this embodiment after being continuously heated at high temperature for 2 minutes. Fig.10 It can be seen that the clover did not show obvious shrinkage or carbonization, indicating that the aerogel material has excellent thermal insulation properties.
[0072] Fig.11 The temperature change state diagram and curve diagram of the aluminum oxide boron nitride fiber skeleton aerogel material with a thickness of 20 mm prepared in this embodiment during the heating process of 1min to 30min, from Fig.11 It can be seen that the temperature of the front side of the aerogel material has been maintained at around 1200°C, while the temperature of the back side was detected to reach a maximum of 170°C at 15min to 20min. The temperature difference between the front and back sides of the aerogel material can reach 1030°C, indicating that the aerogel material has excellent thermal insulation properties and can withstand high-temperature ablation for up to half an hour.
[0073] Fig.12 This is a scene diagram of the thermal insulation flexible felt prepared from the aluminum oxide boron nitride fiber skeleton aerogel material prepared in this embodiment for use in thermal insulation, from Fig.12 It can be seen that the aerogel wrapped in the carton has good anti-ablation performance, indicating that the aerogel material has excellent thermal insulation performance in flammable or high-temperature environments.
[0074] Example 4
[0075] like Figure 1 As shown, this embodiment includes the following steps:
[0076] Step 1, preparation of boron nitride aerogel: at room temperature, 2.1g of boric acid and 2.1g of melamine were dissolved in 8.9mL of distilled water to obtain a precursor solution, and then the precursor solution was heated to 85°C and continuously stirred until the system became transparent. When cooled to room temperature, it presented a white gel-like emulsion. After standing, it was inverted and observed. The system lost fluidity, and a boron nitride precursor was obtained. The temperature was maintained at 35°C to 40°C. The boron nitride precursor was placed in a refrigerator at -5°C for 72h, and then freeze-dried for 24h to obtain a boron nitride aerogel precursor composed of micro-nanobelts, which was then placed in a tubular furnace, heated to 1200°C at a heating rate of 10°C / min, and then kept warm for 4h, and naturally cooled to room temperature to obtain a boron nitride aerogel;
[0077] Step 2, prepare a super concentrated emulsion: at room temperature, disperse 10 mg of mullite fiber into 5 mL of a 5% polyethyleneimine aqueous solution for mixing, oscillating and ultrasonicating, and use amino groups to surface modify the mullite fiber for 120 minutes, and the system is transformed into a light yellow transparent solution to obtain modified alumina fiber, and then 0.13 g of the boron nitride aerogel obtained in step 1 and 0.48 g of the modified alumina fiber solution are ultrasonically dispersed in 1 mL of a 20% polyvinyl alcohol aqueous solution, and stirred and mixed at a high speed of 450 rpm to obtain a super concentrated emulsion;
[0078] Step 3. Prepare alumina boron nitride fiber skeleton aerogel material: place the superconcentrated emulsion obtained in step 2 in a -5°C refrigerator for 40 hours, then freeze-dry for 48 hours, and then heat the freeze-dried product to 800°C at a heating rate of 5°C / min and keep it for 4 hours for high-temperature pyrolysis to obtain alumina boron nitride fiber skeleton aerogel material.
[0079] After testing, the density of the aluminum oxide boron nitride fiber skeleton aerogel material prepared in this embodiment is 0.29g / cm 3 The porosity is 92.1% and the thermal conductivity is 27.3mW / (m·K).
[0080] The boron source small molecule in this embodiment may also be one or more of boric acid, boric anhydride and sodium borate other than boric acid, the nitrogen source small molecule may also be one or more of urea, melamine and polyethyleneimine other than melamine, and the solvent may also be one or more of distilled water, ethanol and tert-butanol other than distilled water.
[0081] Fig.13 The thermal conductivity curves of the aerogel materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1 are shown in FIG. Fig.13 It can be seen that from Fig.13 It can be seen that the thermal conductivity of the boron nitride fiber skeleton aerogel material prepared in Comparative Example 1 is higher than that of the alumina boron nitride fiber skeleton aerogel material prepared in Examples 1 to 4, indicating that the alumina fibers and the boron nitride fibers form an aerogel material that is entangled with each other. The entangled three-dimensional network structure gives the aerogel material a rich pore structure and a three-dimensional network, forming the internal structure of the aerogel material. Generally, there are three main ways of heat transfer in aerogel materials: heat conduction, heat convection, and heat radiation. In porous materials, heat conduction plays a key role. When the pore size increases, the connections between the solid skeletons become thicker, the path for heat conduction along the solid skeleton is smoother, and the heat can travel more smoothly, making heat conduction easier. Therefore Fig.13As the content of boron nitride and alumina fibers increases, the three-dimensional network structure of the aerogel material is entangled with each other, the three-dimensional structure is richer, but the pores are reduced, and its thermal conductivity is reduced, and even the thermal conductivity of the aerogel material is lower than that of the alumina fiber. When the content is 40%, because the alumina fiber has strong rigidity, the network skeleton between the aerogel material and the boron nitride fiber is looser than when the content is 30%, so the thermal conductivity of the aerogel material increases.
[0082] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super concentrated emulsion, characterized in that: The method comprises the following steps: Step 1, preparing boron nitride aerogel: at room temperature, mixing a boron source small molecule, a nitrogen source small molecule and a solvent to obtain a precursor solution, then shaking the precursor solution and subjecting it to low temperature treatment, triggering a sol-gel transition by temperature induction, obtaining a boron nitride precursor, and then freeze-drying and high-temperature pyrolysis the boron nitride precursor to obtain a boron nitride aerogel; Step 2, preparing a super concentrated emulsion: at room temperature, dispersing alumina fibers into a polyethyleneimine aqueous solution, modifying the surface of the alumina fibers using amino groups to obtain modified alumina fibers, and then dispersing the boron nitride aerogel obtained in step 1 and the modified alumina fibers into a polyvinyl alcohol aqueous solution and mixing them with high-speed stirring to obtain a super concentrated emulsion; Step 3: Prepare alumina boron nitride fiber skeleton aerogel material: place the super concentrated emulsion obtained in step 2 in a mold for ice template freezing, then freeze-dry, and then pyrolyze the freeze-dried product at high temperature to obtain alumina boron nitride fiber skeleton aerogel material.
2. The method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super concentrated emulsion according to claim 1, characterized in that: In step 1, the boron source small molecule is selected from one or more of boric acid, boric anhydride and sodium borate, the nitrogen source small molecule is selected from one or more of urea, melamine and polyethyleneimine, and the solvent is selected from one or more of distilled water, ethanol and tert-butanol.
3. The method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super concentrated emulsion according to claim 1, characterized in that: The preparation process of the precursor solution in step one is: dissolving the boron source small molecules and the nitrogen source small molecules in a solvent, heating to 80°C~85°C and continuously stirring to obtain a precursor solution, and maintaining the precursor solution at 35°C~40°C; the low-temperature treatment process is: keeping warm below -5°C for more than 10 hours; the freeze-drying time is greater than 24 hours; the high-temperature pyrolysis process is: heating to 1000°C~1200°C at a heating rate of 5°C / min~10°C / min and keeping warm for 3h~4h.
4. The method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super concentrated emulsion according to claim 1, characterized in that: The mass fraction of the polyethyleneimine aqueous solution in step 2 is 1% to 5%.
5. The method for constructing alumina boron nitride fiber skeleton aerogel material based on super concentrated emulsion according to claim 1, characterized in that: The mass of the modified alumina fiber in step 2 is less than 40% of the mass of the polyvinyl alcohol aqueous solution, and the mass fraction of the polyvinyl alcohol aqueous solution is 5% to 20%.
6. The method for constructing alumina boron nitride fiber skeleton aerogel material based on super concentrated emulsion according to claim 1, characterized in that: In step 2, the boron nitride aerogel and the modified alumina fibers are dispersed in a polyvinyl alcohol aqueous solution by ultrasonic dispersion, and then mechanically stirred and polymerized at a rotation speed of 350 to 450 rpm.
7. The method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super concentrated emulsion according to claim 1, characterized in that: The mass ratio of the boron nitride aerogel to the modified alumina fiber in step 2 is 13:16-48.
8. The method for constructing an alumina boron nitride fiber skeleton aerogel material based on a super concentrated emulsion according to claim 1, characterized in that: The high temperature pyrolysis process in step 3 is: heating to 1000°C to 1200°C at a heating rate of 5°C / min to 10°C / min and then keeping warm for 3h to 4h.
9. The method for constructing alumina boron nitride fiber skeleton aerogel material based on super concentrated emulsion according to claim 1, characterized in that: By adjusting the mass ratio of the boron nitride aerogel to the modified alumina fiber in step 2, the porosity is adjusted by utilizing supramolecular assembly electrostatics to control the entanglement of the skeleton structure of the modified alumina fiber and the boron nitride aerogel.
Citation Information
Patent Citations
Preparation method of ceramic fiber reinforced SiO2-TiO2 aerogel heat insulation composite material
CN114716259A
Alumina suspension for plasma spraying and preparation method and application thereof
CN118755288A